An Investigation of Bilateral Symmetry in Softball Pitchers According to Body Composition - Friesen, Kenzie B.; Lang, Angelica E.; Chad, Karen E.; Oliver, Gretchen D. (Frontiers in Sports and Active Living, 2022)
Introduction: High body fat percentage is considered a potential injury risk factor for softball pitchers amidst the already high rates of pitching-related injury. Similarly, research notes large bilateral asymmetries are another risk factor for softball pitchers. Because softball pitching is a highly asymmetric sport, and the repetitive nature of the windmill pitch places high stress on the body while pitchers are in unbalanced and asymmetric positions, research examining body composition and asymmetry is necessary. Purpose: The purpose of this study was to compare functional characteristics of softball pitchers with a healthy and a high body fat percentage. Bilateral symmetry was assessed for pitchers’ hip and shoulder isometric strength (ISO) and range of motion (ROM) between two groups of softball pitchers: 1) those with a high body fat percentage (≥ 32%); and 2) those with a healthy body fat percentage (< 32%). Methods: Forty-one high school female softball pitchers from the southern United States agreed to participate (1.69±.07m, 76.14±17.08kg, 15.1±1.1years). Pitchers completed a dual-energy x-ray absorptiometry (DEXA) scan and were grouped into one of two categories based on their body fat percentage (bf%): healthy (< 32 bf%) and high (≥ 32bf%). Bilateral symmetry was assessed for pitchers’ hip and shoulder isometric strength (ISO) and range of motion (ROM) using a handheld dynamometer and inclinometer, respectively. Bilateral arm bone and lean mass was also measured via the DEXA. Results: Mixed analyses of variance revealed a significant interaction between body fat percentage groups and side dominance for internal rotation shoulder ROM, F(1,39)=14.383, p<.001, η2p=.269. Main effects for side dominance were also observed for shoulder external rotation ISO, F(1,39)=8.133, p=.007, η2p=.173, hip internal rotation ISO, F(1,39)=4.635, p=.038, η2p=.106, arm bone mass, F(1,39)=38.620, p<.001, η2p=.498, and lean arm mass, F(1,39)=101.869, p<.001, η2p=.723. Conclusions: Asymmetries and slight differences in functional characteristics exist between body fat percentage groups. Altered functional characteristics may influence pitchers’ windmill pitch movement and should be acknowledged by support staff to improve softball pitchers’ health and longevity. Implications: Insight into asymmetries can help researchers and clinicians understand the implication of excess body fat and further theorize mechanisms of injury among this athlete population.